2021
DOI: 10.1177/14574969211011032
|View full text |Cite
|
Sign up to set email alerts
|

Changing Paradigms in the Management of Acute Uncomplicated Diverticulitis

Abstract: Left-sided colonic diverticulitis is a common condition with significant morbidity and health care costs in Western countries. Acute uncomplicated diverticulitis which is characterized by the absence of organ dysfunction, abscesses, fistula, or perforations accounts for around 80% of the cases. In the last decades, several traditional paradigms in the management of acute uncomplicated diverticulitis have been replaced by evidence-based routines. This review provides a comprehensive evidence-based and clinical-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…No longer based primarily on number of attacks, colectomy is generally recommended for complicated diverticulitis, whereas patients with recurrent uncomplicated disease merit individualized discussion and shared decision-making. 1 The risks of surgery are well established, 2 but the benefits are less clear. Therefore, the burden of proof falls on us: does surgery improve short-and longterm gastrointestinal function in patients with multiple episodes of diverticulitis?…”
Section: Role Of the Funder/sponsormentioning
confidence: 99%
See 2 more Smart Citations
“…No longer based primarily on number of attacks, colectomy is generally recommended for complicated diverticulitis, whereas patients with recurrent uncomplicated disease merit individualized discussion and shared decision-making. 1 The risks of surgery are well established, 2 but the benefits are less clear. Therefore, the burden of proof falls on us: does surgery improve short-and longterm gastrointestinal function in patients with multiple episodes of diverticulitis?…”
Section: Role Of the Funder/sponsormentioning
confidence: 99%
“…Acute diverticulitis is a common reason to seek emergency medical attention . At least two-thirds of the episodes are uncomplicated, but a subset of patients present with complicated diverticulitis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Recently, it has been suggested that colonoscopy might not be necessary after an episode of uncomplicated acute diverticulitis, but it is indicated in patients with complicated disease. 11–15 However, in the literature, there are few studies with long-term follow-up on this issue. 16…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recently, it has been suggested that colonoscopy might not be necessary after an episode of uncomplicated acute diverticulitis, but it is indicated in patients with complicated disease. [11][12][13][14][15] However, in the literature, there are few studies with long-term follow-up on this issue. 16 The objective of this study was to analyze whether further colonic examination is worthwhile for ruling out malignancy after CT-diagnosed acute diverticulitis.…”
Section: Introductionmentioning
confidence: 99%